Effect of different bleaching protocols on the color and translucency parameters of a new monochromatic universal composite resin - Mohammad Esmaeel Ebrahimi Chaharom; Mahmoud Bahari; Soodabeh Kimyai; Helia Bagban Nikzad (Journal of Dental Research, Dental Clinics, Dental Prospects)
Background. Considering the few studies on the effect of bleaching protocols on the color properties of a newly developed monochromatic universal composite resin, the present study evaluated the effect of different bleaching protocols on the color change and translucency of Omnichroma (OMN) composite resin. Methods. In this laboratory study, 45 cylindrical OMN composite resin disks with a diameter of 10 mm and a thickness of 2 mm were used. The samples were randomly divided into three groups (n=15) based on the bleaching protocols: group 1: 40% hydrogen peroxide (HP) for 20 minutes, twice a day for three sessions one week apart; group 2: 20% carbamide peroxide (CP) for 8 hours a day, for 14 consecutive days; group 3: 40% HP with Nd:YAG laser (HP+Nd:YAG laser) applied on the gel for 30 seconds twice. Baseline and post-bleaching measurements of color parameters were done using a Vita Easyshade spectrophotometer. Data was analyzed using paired-samples t-test, one-way ANOVA, and post hoc Tukey tests (P<0.05). Results. All the bleaching protocols significantly changed the color (P<0.001) and translucency (P<0.001) parameters. CP caused the most color changes (P<0.05) and translucency (P<0.05), which were significant, and color and translucency changes caused by HP and HP+Nd:YAG laser were not significant (P>0.05). Conclusion. Bleaching caused a noticeable change in the color and translucency of the OMN composite resin. The effect of the at-home bleaching protocol was greater than the in-office ones.